The Role of ICT-Based Learning Media in Improving the Quality of Islamic Religious Education Learning: A Study on the Use of Artificial Intelligence at MAN 2 East Aceh - Mardhiah, Ainul; Zulkarnaini, Zulkarnaini; Hanum, Lathifah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2025)
This study addresses the increasing necessity for madrasahs to modify teaching methodologies in accordance with the requirements of 21st-century education, while maintaining fundamental Islamic spiritual values. The objective is to analyze the implementation, pedagogical advantages, and obstacles of incorporating Information and Communication Technology (ICT) and Artificial Intelligence (AI)–based learning media in Akidah Akhlak education at Madrasah Aliyah Negeri (MAN) 2 Aceh Timur. Utilizing a qualitative field research design, data were collected through systematic observations, comprehensive interviews, and document analysis including the school principal, Akidah Akhlak educators, and tenth-grade students. The data analysis comprised steps of reduction, data presentation, and conclusion formulation, utilizing triangulation to guarantee validity and trustworthiness. The results demonstrate that the utilization of digital platforms like Google Classroom, YouTube, Canva, and Quizizz, in conjunction with AI-driven applications such as ChatGPT and Islamic educational platforms, markedly improved students' motivation for learning and their comprehension of Islamic beliefs and ethical principles. These technologies empowered educators to convert abstract theological notions into more visible, contextual, and interactive learning experiences. Nonetheless, the survey revealed other problems, such as inadequate technological infrastructure, unreliable internet connectivity, and disparate levels of digital proficiency among educators and learners. These limits were mitigated by institutional initiatives including ongoing training, mentorship programs, and incremental enhancement of infrastructure. The amalgamation of ICT and AI enhances students' digital literacy while simultaneously fortifying spiritual literacy, so establishing technology as a potent instrument for reinforcing the principles of ta‘l?m, ta’d?b, and tarbiyah in modern Islamic education.